Effects of Ramadan Fasting on Lipid Profiles and Interleukin-6 in Obese Patients: Effects of Ramadan Fasting on Lipid Profiles and Interleukin-6 in Obese Patients - Lubis, Frihastina; Muhammad Aron Pase (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2020)
Abstract. Obesity can cause a state of chronic low-grade inflammation due to hypertrophy and hyperplasia of adipose tissue which is not followed by the formation of balanced vascularization. Interleukin-6 is one of the mediators of inflammation that results from obesity. Changes in lifestyle during fasting for the entire month of Ramadan are thought to have an effect on the lipid profile and inflammatory mediators. Method. This research is a prospective cohort observational study conducted in March 2019-May 2019 endocrine polyclinic outpatient clinic Haji Adam Malik Hospital Medan in 30 subjects. Anthropometric measurements and examination of lipid profiles and IL-6 levels, one week before Ramadan fasting and the fourth week of Ramadan. Results. This study showed that there were significant differences in total cholesterol and HDL levels in the study subjects before and after Ramadan fasting (p <0.001; p = 0.049). Also found significant differences in median IL-6 study subjects before and after Ramadan fasting (p <0.001). Conclusion. There was a decrease in levels of IL-6, a decrease in total cholesterol and a statistically significant increase in HDL in obese patients undergoing Ramadan fasting.